Cytotoxic T lymphocyte responses in HIV-1-infected long-term nonprogressors: lessons for vaccine design. (July 2008) - Navis, Marjon; Miedema, Frank; Schuitemaker, Hanneke
Cytotoxic T lymphocytes (CTLs) are considered to play an important role in the containment of HIV-1 infection. Their efficacy is, however, limited as they also continuously select for HIV-1 variants with escape mutations in CTL epitopes. Moreover, it remains to be established whether the preservation of high frequencies of HIV-1-specific CTLs in long-term nonprogressive HIV-1 infection are the cause or consequence of controlled HIV infection. On the positive side, some escape mutations seem to come at a fitness cost to the virus, which may imply that some CTLs, by selecting HIV-1 variants with reduced replication competence, still contribute to a reduced viral load. The implications of current knowledge on HIV-specific cellular immunity for vaccine development will be discussed.